Pengukuran Kerja di UMKM Penggilingan Padi di Payakumbuh dengan Metode Studi Waktu - Winny Alna Marlina; Fani Ramadhani; Armijal (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
MSMEs Heler Sari is one of the rice millers in Payakumbuh, West Sumatera. In running a rice milling business, the owner has never measured the standard time of workers, so the management cannot determine the optimal number of workers. This research aims to measure the standard time of workers in MSMEs as a consideration for owners in optimising productivity by paying attention to allowances and worker factor ratings. This research is quantitative with a time study approach using a stopwatch as the primary data source. The research results showed that the standard time for each work element for lifting grain was 6.023 minutes, drying grain 10.2 minutes, putting grain into sacks 7.264 minutes, putting grain into the mill 11.373 minutes, sewing rice sacks 1.928 minutes, putting rice into sacks 3.489 minutes, lifting rice to storage 3.89 minutes. 3.89 minutes. Measuring work is very important, especially knowing the standard times of work components. Increasing productivity can reduce time and costs and achieve production goals.